Evaluation of spirulina fusiformis as a protein source in the diet of penaeus monodon fabricius - Tank Ketan Vallabhdas (Department of Aquaculture, College of Fisheries, 2008)
The blue green alga Spirulina fusiformis has been accepted as an ideal food organism since it has a high protein content of 60-65 %, besides being rich in vitamins, minerals, fatty acids (gamma-linolenic acid (GLA)) and antioxidant pigments such as carotenoids. The present study is aimed at finding out the feasibility of using Spirulina fusiformis as a protein source in the diet for black tiger shrimp Penaeus monodon (Fabricius). Six isonitrogenous test diets T1 to T6 were prepared with 40% crude protein. Clam meat was replaced with Spirulina at an inclusion level of 5%, 10%, 20%, 30% and 40%, and the substitution effect was compared with a control diet in which clam meat was the sole source of protein. The study was conducted for a period of 60 days employing Penaeus monodon postlarvae (0.04 g avg. weight) with six treatments and four replications. The postlarvae were stocked at the rate of 10 numbers per tank. On completion of the experiment the specific growth rate, food conversion ratio and protein efficiency ratio were superior in shrimp postlarvae fed with the test diet containing 20% Spirulina. The diet T4 (20% Spirulina) led to significantly higher growth response (p>0.05) than in other diets. Further increase in the Spirulina inclusion levels significantly decreased the growth and feeding performance. The highest SGR (6.82%) and PER (1.67) were recorded with diet T4 and lowest SGR (4.16%) and PER (0.62) were obtained with the dietT6. The percentage survival was significantly higher (97.5%) in T3 (10% Spirulina) and T4 (20% Spirulina). The best FCR was recorded for 20% Spirulina (1.49). The results suggest that Spirulina fusiformis cannot serve as the sole protein source in the diet of Penaeus monodon postlarvae but can be effectively used as a supplementary protein source.